Enzymatic hydrolysis of poly(1, 4-butylene 2, 5-thiophenedicarboxylate) (PBTF) and poly(1, 4-butylene 2, 5-furandicarboxylate) (PBF) films: A comparison of mechanisms. (September 2019) - Gigli, Matteo; Quartinello, Felice; Soccio, Michelina; Pellis, Alessandro; Lotti, Nadia; Guebitz, Georg M.; Licoccia, Silvia; Munari, Andrea
Abstract: Enzymatic hydrolysis of poly(1, 4-butylene 2, 5-thiophenedicarboxylate) (PBTF) and poly(1, 4-butylene 2, 5-furandicarboxylate) (PBF) by Humicola insolens (HiC) and Thermobifida cellulosilytica (Cut) cutinases is investigated. For the first time, the different depolymerization mechanisms of PBTF ( endo -wise scission) and PBF ( exo -wise cleavage) has been unveiled and correlated to the chemical structure of the two polyesters. Highlights: PBF and PBTF were successfully hydrolyzed by cutinase enzymes. Weight losses of about 20% have been reached after only 72 h of incubation. Different depolymerization mechanisms of PBTF ( endo -wise scission) and PBF ( exo -wise cleavage) were unveiled.